2020
DOI: 10.3390/e22121430
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Observing Ionic Coulomb Blockade in Artificial Ion Confinements

Abstract: Nanofluidics encompasses a wide range of advanced approaches to study charge and mass transport at the nanoscale. Modern technologies allow us to develop and improve artificial nanofluidic platforms that confine ions in a way similar to single-ion channels in living cells. Therefore, nanofluidic platforms show great potential to act as a test field for theoretical models. This review aims to highlight ionic Coulomb blockade (ICB)—an effect that is proposed to be the key player of ion channel selectivity, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The ultralow flux of ions in narrower channels with higher σ corresponds to Coulomb blockade induced by electrostatic interactions, and this phenomenon has in fact been predicted for low-capacitance, water-filled, charged ion channels. 50,51…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ultralow flux of ions in narrower channels with higher σ corresponds to Coulomb blockade induced by electrostatic interactions, and this phenomenon has in fact been predicted for low-capacitance, water-filled, charged ion channels. 50,51…”
Section: Resultsmentioning
confidence: 99%
“…The ultralow flux of ions in narrower channels with higher s corresponds to Coulomb blockade induced by electrostatic interactions, and this phenomenon has in fact been predicted for low-capacitance, waterfilled, charged ion channels. 50,51 As we have discussed for Fig. 2, the present ion selectivity should be codetermined by both the channel geometry and electrostatic interactions.…”
Section: Rectification Reversion At High Surface Charge Densitymentioning
confidence: 90%
See 1 more Smart Citation
“…20,30,47 Although the large modulation of ionic transport due to partial delamination is similar to the case of pressure induced nanoparticle blockages 47 and could be used to produce more robust mechanical pressure sensors, it is still far away from true mechanosensitivity where ion transport is modulated by mechanical stress directly modulating the energy barriers for single ion translocations. 46,48 Our approach allows a better understanding of measurements with supported 2D materials, i.e. avoiding misinterpreting the measured data and could be used to probe how the electrical field and fluid flow at the nanoscale would influence membrane adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The work by A. Chernev et al [ 13 ] reviews the most promising approaches to the fabrication of artificial nanofluidic devices capable of reproducing the properties of single ion channels. It is shown that modern technologies have great potential in allowing one to test various theoretical models of ion channels.…”
mentioning
confidence: 99%